Improving Reading Comprehension Through the Use of Quizizz Technique - Siti Fatimah (PGRI Provinsi Jawa Timur, 2022)
This research was conducted to describe the implementation of Quizizz and the students’ reading comprehension improvement on teaching reading comprehension for the 9th grade students at SMPN 44 Surabaya. Classroom Action Research (CAR) was applied to the 39 students at class 9-A. The observation and tests were the instruments used. It was done in two cycles. In pre-research, there were only 14 students who passed the test, representing a success rate of 35.90%. While 22 students (56.41%) were able to pass the test, the remaining students failed (17 students) in cycle 1. the numbers of students who passed the test were improving from 22 students (cycle 1) to 34 students (cycle 2). It can be argued the numbers of students increased in the percentage of 86.18%. Students’ reading comprehension has significantly improved as a result of the implementation of the Quizizz application to 9th grade students at SMPN 44 Surabaya in the academic year 2020/2021, and this finding supports the major hypothesis of the research that students' reading comprehension has significantly improved.